Bioconduit subannular implantation for aortic root endocarditis after previous cardiac surgery: Results from two Italian centers. Issue 11 (21st August 2020) - Cefarelli, Mariano; Concistrè, Giovanni; Montecchiani, Luca; Bianchi, Giacomo; Berretta, Paolo; Margaryan, Rafik; Alfonsi, Jacopo; Murzi, Michele; Solinas, Marco; Di Eusanio, Marco
Abstract: Objectives: Infective endocarditis (IE) with extensive peri‐annular abscesses and aortic root involvement is a life‐threatening disease. Aortic root replacement with a valved conduit is the most common intervention in this setting and represents a serious challenge for the surgeon. In the present two‐center study we analyzed early and midterm outcomes of a high‐risk series of IE patients undergoing aortic root reconstruction with a sub‐annular implantation of a totally biological valved conduit at our centers. Methods: The series comprised 29 patients (18 males, mean age: 72.3 ± 10.1 years) operated at "Lancisi Cardiovascular Center" of Ancona and "Pasquinucci Heart Hospital" of Massa, Italy, between May 2016 and October 2019. All patients had undergone a previous cardiac surgery. Median Euroscore‐II was 12.6%. Following aggressive debridement, a Bioconduit was implanted using a sub‐annular implantation technique in all cases. Results: Thirty‐day mortality was 13.8% (n = 4). Multiorgan failure was cause of death in all cases. Respiratory complications occurred in eight patients (27.6%). Renal complications requiring temporary or permanent dialysis occurred in six (20.7%) and two (6.9%) patients, respectively. Mortality and morbidity were not related to the surgical approach. At 1‐year follow‐up three patients died and no patients underwent reoperation neither reported endocarditis of the biological conduit. Conclusion: Considered the high‐risk profile of the study cohort, our results suggest safety and efficacy of our approach at 1‐year. Indeed, we contend that our subannular implantation of a 100% pericardial valved conduit, allowing an effective abscess exclusion and a conduit anchoring to healthy tissues, can reduce the risk of reinfection and dehiscence.